2021
DOI: 10.4078/jrd.2021.28.4.234
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Biomarkers With Pulmonary Involvement of Rheumatoid Arthritis Interstitial Lung Disease: From KORAIL Cohort Baseline Data

Abstract: Objective. The increase in mortality in rheumatoid arthritis (RA) patients with interstitial lung disease (ILD) is well known. However, there are few studies on serum markers that can evaluate acute exacerbation or prognosis in RA-ILD patients. The purpose of this study was to identify the association between biomarkers and lung lesions in patients with RA-ILD. Methods. We analyzed 153 patients with serum samples in a prospective, multicenter cohort of Korean RA-ILD patients. The serum levels of biomarkers, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Additionally, MMP-7 levels correlated with the semi-quantitative grade of CT. Thus, the authors suggested that MMP-7 can be used to measure the functional and anatomical status of lungs in patients with RA-ILD [147].…”
Section: Emtmentioning
confidence: 99%
“…Additionally, MMP-7 levels correlated with the semi-quantitative grade of CT. Thus, the authors suggested that MMP-7 can be used to measure the functional and anatomical status of lungs in patients with RA-ILD [147].…”
Section: Emtmentioning
confidence: 99%
“…Biomarkers, such as serum ACPAS, MMP7, and CXCL10, and some heat shock proteins have been identified. In the KORAIL Cohort Baseline Data study, not only MMP7, but also SP-D and KL-6 were found to be useful for evaluating the functional and anatomical status of lung involvement in patients with RA-ILD [ 57 ]. However, these biomarkers are currently not used in clinical practice [ 58 , 59 ].…”
Section: Clinical Aspects Of Ra-ildmentioning
confidence: 99%
“…The classification criteria for systemic sclerosis (SSc) include ILD [ 7 ]. Although classification criteria for SSc includes ILD as one item as classification criteria, however, other autoimmune diseases, such as rheumatoid arthritis (RA), inflammatory myositis, primary Sjögren’s syndrome (pSS), and systemic lupus erythematosus (SLE) can also present with ILD [ 3 , 8 ]. Nailfold capillaroscopy (NFC) can detect abnormalities in microcirculation, and abnormal findings of NFC are mainly found in patients with SSc [ 9 ].…”
Section: Introductionmentioning
confidence: 99%